Association Bone Schintigraphy with Prostate Spesific Antigen, Gleason score, and Grade group in Prostate Cancer Patient - Reza Rinaldy Harahap; Achmad Hussein Sundawa Kartamihardja; Basuki Hidayat; Hendra Budiawan; Budi Darmawan; Raden Erwin Affandi Soeriadi Koesoemah (Unram Medical Journal, 2022)
Background. Metastasis (especially in bone) in prostate cancer is often difficult to diagnose and poor prognosis. Hence, it is very important to do an early examination in detecting metastasis. Frequent bone scintigraphy indicators are prostate specific antigen (PSA) level and Gleason score (GS). This study aims to analyze how strong correlation of these factors in affecting bone metastasis in prostate cancer. Subject and method. A retrospective cross-sectional analysis study was performed using medical records of the prostate cancer patients who underwent Tc-99m MDP bone scintigraphy at Hasan Sadikin General Hospital during January 2012 until December 2016. PSA level, GS and Gleason grade (GG) data were analyzed by bivariate and multivariate analysis. Result. From 189 medical records, only 110 medical records were eligible to be analyzed. Bivariate analysis demonstrated statistically significant correlation for PSA level (p <0.001) and GS (p 0.05 and p 0.036) with bone metastasis in prostate cancer. Multivariate analysis showed that PSA remains the strongest factor associated with bone metastasis in prostate cancer (p 0.001). Conclusion. From bivariate analysis, serum PSA level have statistically significant correlation with bone metastasis in newly diagnosed prostate cancer patient. In the GS dan GG classification, the higher-grade of GS or GG the higher bone metastasis in prostate cancer patient. Thus, the above results may be helpful in identifying prostate cancer patients who have a high risk for bone metastasis.